Predictive Factors of Opioid-Induced Nausea in Cancer Patients. (9th April 2021) - Ogawa, Yasuha; Kurihara, Tatsuya; Sakurai, Mami; Monma, Megumi; Nakayama, Hirofumi; Higuchi, Hitomi; Kogo, Mari; Kiuchi, Yuji
Abstract: Approximately 30% of patients experience nausea after initiation of opioid therapy, which can lead to poor quality of life. We aimed to identify risk factors for opioid-induced nausea at the initiation of opioid therapy by conducting a retrospective review of medical records of patients diagnosed by palliative care specialists with solid cancer and pain at the lesion site at Showa University Hospital between June 2005 and June 2011. The primary endpoint was the development of nausea grade ≥1 according to the Common Terminology Criteria for Adverse Events version 4.0 within 48 hours of initiation of opioid therapy. The median age of the 134 enrolled patients was 67.7 (range 28–95) years. Fifty-three percent were male and 44% had gastrointestinal cancer. Furthermore, 22.4% had opioid-induced nausea. Age (odds ratio (OR) 1.74; 95% confidence interval (CI), 1.13–2.69), edema (OR 5.83; 95% CI, 1.22–28.19), and gastrointestinal cancer (OR 2.61, 95% CI 1.07–6.36) were significantly associated with opioid-induced nausea. Prophylactic antiemetics were found to be ineffective.